Investigation of used Conveyor Belts by the Differential Scanning Calorimetry Analysis - Lucia Knapcikova (TEM Journal, 2016)
In this paper is presented the use of differential scanning calorimetry analysis of the used conveyor belts. This method has been specifically tested on the individual components contained in the used conveyor belts esp. rubber pellets, cord and fabric. The result of the analysis is the determination of Tg temperature and melting temperatures (Tm) by the components.Weanalyzed used conveyor belts and after this analysis it was determined components and their application to the industry